Perbandingan Klitik Pronomina Bahasa Sasak dengan Bahasa Indonesia - Muh Ardian Kurniawan (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2018)
This research aims at describing comparison of pronoun clitic of Sasak language and bahasa using contrastive linguistics analysis. So far, contrastive linguistics is more used to contrast non- cognate languages. Furthermore, this research tries to compare cognate languages, they are Sasak and bahasa. Listening and leading proficiency method were used in collecting data while intralingual equivalent was used in analyzing data. The result shows that there is difference between Sasak n bahasa pronouns clitic. It s identified by Sasak clitic is only as enclitic while bahasa can be both proclitic and enclitic. Another difference is that Sasak clitics always attach to the host word, while bahasa, clitic can be used separately with the host word. Besides, for further review, this pronoun clitic comparison will implicate didactically, especially in Sasak learning to bahasa learner of local material in elementary n junior high school level, and vice versa.